A DRD4 gene by maternal sensitivity interaction predicts risk for overweight or obesity in two independent cohorts of preschool children. (11th October 2016) - Levitan, Robert D.; Jansen, Pauline; Wendland, Barbara; Tiemeier, Henning; Jaddoe, Vincent W.; Silveira, Patricia P.; Kennedy, James L.; Atkinson, Leslie; Fleming, Alison; Sokolowski, Marla; Gaudreau, Helene; Steiner, Meir; et al.
Abstract : Background: Recent evidence suggests that early exposure to low maternal sensitivity is a risk factor for obesity in children and adolescents. A separate line of study shows that the seven‐repeat (7R) allele of the dopamine‐4 receptor gene (DRD4) increases susceptibility to environmental factors including maternal sensitivity. The current study integrates these lines of work by examining whether preschoolers carrying the 7R allele are more vulnerable to low maternal sensitivity as it relates to overweight/obesity risk. Method: The Maternal Adversity Vulnerability and Neurodevelopment (MAVAN) project in Canada was used as the discovery cohort ( N  = 203), while the Generation R study in the Netherlands was used as a replication sample ( N  = 270). Regression models to predict both continuous BMI z ‐scores and membership in any higher BMI category based on established World Health Organization (WHO) cutoffs for 48 months of age were completed. Results: In both cohorts, there was a significant maternal sensitivity by DRD4 by sex interaction predicting higher body mass indices and/or obesity risk. As hypothesized, post hoc testing revealed an inverse relationship between maternal sensitivity and body mass indices in 7R allele carriers relative to noncarriers. This finding was strongest in girls in the Canadian cohort and in boys in the Dutch cohort. Conclusions: Many children who carry the 7R allele of DRD4 appear to be more influenced by maternal sensitivity as it relates to overweight/obesity risk, consistent with a plasticity effect. Given the relatively small sample sizes available for these analyses, further replications will be needed to confirm and extend these results.